The potential of an integrated pharmaceutical care model with telepharmacy in adherence and knowledge about pharmacological treatment in patients with mental disorders: A clinical trial - Núbia Cristina Burgo Godoi de Carvalho; Ana Carolina Figueiredo Modesto; Mércia Pandolfo Provin (Brazilian Journal of Pharmaceutical Sciences)
Abstract The level of understanding about disease and treatment is an important factor to consider in achieving favorable outcomes in patients with mental disorders, and adherence to pharmacological treatment is crucial in this regard. The aim of this study was to assess to what extent patients with MD undergoing an integrated pharmaceutical care model with telepharmacy showed improvements in factors related to treatment adherence and their level of knowledge about pharmacotherapy. A parallel randomized clinical trial was conducted with a two-arm study in two Psychosocial Care Centers located in a state capital in Brazil. Participants in the intervention group received a comprehensive pharmaceutical care model that included attitudinal, technical, and educational interventions, while the control group received standard routine care. Predictive factors for adherence to pharmacological treatment and level of medication knowledge were assessed before and after the intervention. In the intervention group (33), significant improvements were found in the scores of adherence predictors (p<0.001) and the level of knowledge of pharmacotherapy (p<0.001) from baseline to follow-up, compared to the control group (33). The telepharmacy model demonstrated effectiveness in enhancing the scores of adherence predictors for pharmacological treatment and improving the level of knowledge of pharmacotherapy among patients with mental disorders.